Investigation on boron and iodine behavior during nuclear glass vapor hydration - Haohan Zhang (Nature Portfolio, 2021)
Abstract Understanding the durability of nuclear glass in the vapor phase is essential for evaluating the long-term safety of the nuclear glass. This work studies the vapor hydration of borosilicate and iodine-bearing glass at 90 °C and relative humidity at 99%. Hydration kinetics was monitored by analyzing the boron and iodine released during the vapor hydration process. It is found that boron becomes more easily released after iodine being added to the glass matrix. The results related to boron release and retention indicate the possible transformation of tetrahedral [4]B to trigonal [3]B on the hydrated glass surface, which may enhance the release of boron in the form of boric acid afterward. Release of iodine occurred but at a far lesser extent than boron with 92% of iodine retained in the alteration layer, thus opening good perspectives with regard to the disposal of high-level waste containing iodine.